Development of a loop-mediated amplification (Lamp) assay for detection of environmental Pseudomonas aeruginosa - Nguyen, Thi Phuong Truc; Nguyen, Nhu Ngoc; Lim, Dinh Ky; Huynh, Thuc Quyen; Nguyen, Thi Thu Hoai (Vietnam Journal of Biotechnology, 2024)
Pseudomonas aeruginosa (P. aeruginosa) is a common environmental bacterium found in various habitats, including water and soil. Rapid detection of this microorganism is essential for monitoring environmental contamination and assessing its potential impact on ecosystems and public health. This study aimed to develop a high-efficiency loop-mediated isothermal amplification (LAMP) assay targeting a P. aeruginosa-specific gene encoding a hypothetical protein (GenBank ID: 882161). The study involved two main parts: 1) Isolation and identification of P. aeruginosa from environmental samples, and 2) Evaluation of the established LAMP assay on these environmental P. aeruginosa isolates. A total of 52 samples were collected from various geographical regions in Ho Chi Minh City, with 50 samples (96%) containing Pseudomonas species, characterized as rod-shaped, Gram-negative bacteria growing on selective media. Following duplex PCR screening, 14 P. aeruginosa-like environmental strains were isolated, and 5 randomly selected isolates were confirmed as P. aeruginosa through 16S rRNA sequencing. The LAMP assay was optimized at 60°C, 63°C, and 65°C for 30 and 45 minutes, using specific primers, and tested on all five confirmed P. aeruginosa isolates. The results demonstrated that the LAMP assay was highly specific (100%) for detecting environmental P. aeruginosa, with a detection limit of 1 pg/μL. In conclusion, P. aeruginosa is prevalent in the environment, and the developed LAMP assay shows strong potential for identifying environmental P. aeruginosa isolates.